(3GdJHUQI aj GdfMhs - (3CHh eMeO YHO Gddg Hf Ydj Hf ESMGb GdUjeQj, GHf edchf GdCTHjdj,J (B584 (3g` s ((3eMeO Hf jMji Hf OGhO GdJGOdi s)
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3aVd CYde Cf GdCa hGdjGA ai GdJKfjI hGdhGh hGdjGA ai GdLeY Yf OSjHhjg MQha GdEYQGH HGH GdCaYGd GdeYJdI hMcegG ai GdCYQGH s
(3BNQgG (B:s
(3hGdjGA JOZe ai eKdgG ef cdeJjf EPG faJM eG bHdgG cbhdc GNJTi jGSQkG aGYQag Ef TGA Gddg YR hLd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdfMhs